A New Movement Authority Based on Vehicle-Centric Communication. (4th April 2018) - Shen, Tuo; Song, Haifeng
Abstract : The communication system that is presently applied in the European Train Control System can only support data exchange between vehicles and ground, but the direct vehicle-to-vehicle communication is not available. The details of interlocking information and other vehicles' movements are invisible to drivers who are the last defense to prevent unsafe scenarios. As connected vehicles have been envisioned to enhance transportation efficiency and improve safety, the direct vehicle-to-vehicle communication network is involved in this paper to increase the safety of railway transport. In this paper, a new train movement authority (MA+) is proposed. Apart from a wireless communication unit, this system does not require any other infrastructure. With the assistance of vehicle-centric communication technology, MA+ can detect the condition of switches and trains within a certain scope. In this paper, the system structure of MA+ is proposed. Additionally, different implementation scenarios are also discussed. The detection range is estimated and validated based on mathematical calculation and experimental equations. An application demo of MA+ is presented on the Driver Machine Interface of the onboard equipment. The results indicate that MA+ can be a flexible and scalable system for furthering the improvement of railway safety.